Understanding suicide - Chandler, Matt (21st century skills library. Upfront health., 2020)
Explores the effects of suicide, discussing how untreated and undiagnosed mental illness often is a contributing factor. Provides information on intervention methods to prevent suicide, especially among adolescents, and offers advice on seeking help for mental health issues. Includes photographs, sidebars, a glossary, an index, and resources for further research.